2012
DOI: 10.1007/s10266-012-0085-y
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a handheld nebulizer in cough test to screen for silent aspiration

Abstract: Cough test to screen for silent aspiration (SA) was reported, and the effectiveness was excellent. However, the device was rather large so that the portability was poor. So, the purpose of this study is to investigate the usefulness of a handheld nebulizer for the test and verify the reproducibility of the method. The subjects were 160 patients who were suspected of having dysphagia and underwent videofluorography (VF) or videoendoscopy (VE). They inhaled 1.0 % citric acid-physiologic saline orally for 1 min u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Of 160 patients, 36% had cerebrovascular diseases, 25% neuromuscular diseases, 14% head and neck cancer, 8% respiratory diseases, and 17% other diseases. 38 Once again they obtained good sensitivity, specificity, and predictive valuesd.86, .71, .53 (PPV), and .93 (NPV), respectivelydand concluded that the citric acid cough test using 1.0 (w/v)% is a good standalone method to detect silent aspirators. Disappointingly, our study has not been able to reproduce these results in patients with subacute stroke.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Of 160 patients, 36% had cerebrovascular diseases, 25% neuromuscular diseases, 14% head and neck cancer, 8% respiratory diseases, and 17% other diseases. 38 Once again they obtained good sensitivity, specificity, and predictive valuesd.86, .71, .53 (PPV), and .93 (NPV), respectivelydand concluded that the citric acid cough test using 1.0 (w/v)% is a good standalone method to detect silent aspirators. Disappointingly, our study has not been able to reproduce these results in patients with subacute stroke.…”
Section: Discussionmentioning
confidence: 93%
“…Apart from ethnic differences between Asian and Mediterranean populations and sample heterogeneity, the observed differences cannot be explained by methodological features, and we are unable to find other reasons for this large discrepancy. 13,38,39 The use of a receiver operating characteristic curve based on citric acid cough test peaks to determine the best cutoff points for sensitivity might help to provide an explanation. Unfortunately, we recorded the number of cough spikes as a dichotomous variable (!5 or <5 cough spikes) instead of as a continuous variable, making it impossible to conduct the receiver operating characteristic curve analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The citric acid solution was prepared from the Japanese Pharmacopeia citric acid hydrate (NichiIko Pharmaceutical Co., Toyama, Japan.) and distilled water from our hospital pharmacy, and the nebulizer was the NE-U22 (Handy Type Mesh Nebulizer, Omron Co., Kyoto, Japan) which is easily transported and useful for screening tests [17]. If patient consciousness was low or they were unable to follow instructions due to dementia, a nose clip was employed to encourage them to breathe through the mouth.…”
Section: Methodsmentioning
confidence: 99%
“…The repetitive saliva swallowing test (RSST) [9,10] and the modified water swallow test (MWST) [11,12] are both simple and convenient screening tests for aspiration. In addition to these tests, the simple swallowing provocation test (SSPT) [13] and the cough test [14][15][16][17] are reportedly useful for screening for silent aspiration. However these examinations and screening tests were not developed to predict oral intake capability.…”
Section: Introductionmentioning
confidence: 99%